2021
DOI: 10.1088/1361-6463/ac21fe
|View full text |Cite
|
Sign up to set email alerts
|

The heat equation for nanoconstrictions in 2D materials with Joule self-heating

Abstract: We consider the heat equation for monolayer two-dimensional materials in the presence of heat flow into a substrate and Joule heating due to electrical current. We compare devices including a nanowire of constant width and a bow tie (or wedge) constriction of varying width, and we derive approximate one-dimensional heat equations for them; a bow tie constriction is described by the modified Bessel equation of zero order. We compare steady state analytic solutions of the approximate equations with numerical res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…For such small bias currents, this temperature increase is mostly due to Joule heating and much less due to the Peltier effect. The temperature profile due to Joule heating is given by 49,52 i k j j j y { z z z…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For such small bias currents, this temperature increase is mostly due to Joule heating and much less due to the Peltier effect. The temperature profile due to Joule heating is given by 49,52 i k j j j y { z z z…”
Section: Resultsmentioning
confidence: 99%
“…For such small bias currents, this temperature increase is mostly due to Joule heating and much less due to the Peltier effect. The temperature profile due to Joule heating is given by , T ( x ) = ( F 2 k ) ( s x ) x + T b where T b is the temperature at the boundaries just after the jumps, s is the length of the device, k is the thermal conductivity of graphene, and F = PA –1 is the Joule heating generation term. Since this equation is extracted classically from Fourier’s law and is valid in the diffusive thermal transport regime, we choose to fit only the parabolic part of the temperature profile of the suspended regime (see the curve in the gray shaded part of Figure b) excluding the mini-peaks.…”
Section: Resultsmentioning
confidence: 99%
“…We have performed finite‐element simulations on the planar device geometry and found that 39% of the two‐probe resistance accounts for the central square‐shaped constriction, which is close to 47% derived by analytic expression. [ 29 ] The remaining resistance is due to the tapered NCG regions. Figure 2a shows the resistance of the device R versus the applied bias V for a substrate‐supported and suspended device.…”
Section: Resultsmentioning
confidence: 99%